Plan de inversion para el desarrollo institucional de la cooperativa de taxis macachetax, canton Mocache, periodo 2015-2016 - Ibarra Navarrete, Carmen Johanna (2016)
In this research, study "INVESTMENT PLAN FOR INSTITUTIONAL DEVELOPMENT MOCACHETAX taxi cooperative, Mocache Canton 2015-2016". He pursued the following objectives: to analyze the current situation in the provision of transfer of passengers in the Mocache Canton, establish the elements of the investment plan, assess the viability of the investment plan for the institutional development of the cooperative taxi Mocachetax, to carry out the research project a sample of 380 respondents in this sample the town's taken after the completion of the sample size makes for an infinite population be used, the types of research that are handled are: exploratory field, literature and also the following, observatory, inductive, analytical and synthesis; together a diagnosis of cause and effect of the current situation of the cooperative dare surveys done for the user and interview makes the manager of the institution which provided an insight satisfied and unsatisfied demand in conclusion of agreements to result made it possible to meet little knowledge of the cooperative about making an investment plan, as it is inescapable making an investment to improve the services of the cooperative. However by not remodel the service could be affected cooperative, and this would cause other cooperatives covering the market segment that is being taken. This research is conducted not only in order to raise awareness of the processes that lead to the realization of an investment plan, but also for many companies know that by this study can improve the transport sector, strengthening many other cantons that do not have the remodeling of its services and develop their activities so empirically, based on the things that keep them handy. Keywords: Investment - Improvement - Services.